2017
DOI: 10.1007/s12098-017-2514-y
|View full text |Cite
|
Sign up to set email alerts
|

Etiology and Risk Factors Determining Poor Outcome of Severe Pneumonia in Under–Five Children

Abstract: Staphylococcus aureus and Streptococcus pneumoniae are the predominant organisms causing severe pneumonia in our setting. Children with risk factors such as respiratory rate >70/min, rickets, lethargy/unconsciousness, not able to drink, abnormal chest X-ray or positive blood culture are likely to have a delayed recovery or need of change of antibiotics, whereas those with wheeze are likely to recover faster with less chances of treatment failure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
23
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 10 publications
4
23
0
1
Order By: Relevance
“…The high proportion of infants in our study highlights that infants are particularly vulnerable and prone to hospitalization due to severe pneumonia (Fancourt et al, 2017;Chen et al, 2018;Jakhar et al, 2018). There was no child known or suspected to be infected with HIV, which is consistent with the very low number of underfive year old children infected with HIV in Bhutan (UNAIDS, 2018).…”
Section: Discussionmentioning
confidence: 72%
“…The high proportion of infants in our study highlights that infants are particularly vulnerable and prone to hospitalization due to severe pneumonia (Fancourt et al, 2017;Chen et al, 2018;Jakhar et al, 2018). There was no child known or suspected to be infected with HIV, which is consistent with the very low number of underfive year old children infected with HIV in Bhutan (UNAIDS, 2018).…”
Section: Discussionmentioning
confidence: 72%
“…However, more knowledge on the risk factors affecting the severity of pneumonia is required to reduce deaths from childhood pneumonia. Studies from low/middle-income countries (LMICs) have tried to identify the risk factors for severe pneumonia [ 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 ], but only a few studies from India have reported the risk factors for severe pneumonia [ 6 , 8 , 13 ]. More clinical studies from India are needed as the country alone contributes to 32% of the annual global burden of pediatric pneumonia [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…2 In children with HAP, the conditions were respiration rate >70 x/min, lethargy/unconsciousness, and positive blood culture. 30 It was feared that there were lack information in correlation between response to therapy and mortality, because generally response to therapy was observed simultaneously with mortality as the outcome. This study was the first to analyze risk factors for mortality in children with HAP in Indonesia.…”
Section: Discussionmentioning
confidence: 99%